Hukum Keluarga Islam Irak; Menakar Historis dan Socio Cultural Masyarakat dalam ber-Fiqh - Moh. Mujibur Rohman (ASASI: Journal of Islamic Family Law, 2021)
The development of Islamic law in Muslim countries is undeniable. This development cannot be separated from various conflicts because the state constitution is sometimes not the same as the sharia constitution. Iraq is a country with Muslims who are dominated by two major sects, namely Sunni with the Hanafi school of fiqh and Shi'i with the Ja'fari school of fiqh. The two schools of thought have many legal inconsistencies, especially in terms of inheritance and polygamy, which have very basic differences. In contrast to Egypt, which is easy to codify Fiqh law into law because some schools such as Shafi'i, Hanafi and Maliki do not have significant differences. In its development, Islamic law in Iraq underwent several amendments and a very long history.